2021
DOI: 10.48550/arxiv.2104.12792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CMB $μT$ cross-correlations as a probe of PBH scenarios

Ogan Özsoy,
Gianmassimo Tasinato

Abstract: We propose a new method for probing inflationary models of primordial black hole (PBH) production, using only CMB physics at relatively large scales. In these scenarios, the primordial power spectrum profile for curvature perturbations is characterized by a pronounced dip, followed by a rapid growth towards small scales, leading to a peak responsible for PBH formation. We focus on scales around the dip that are well separated from the peak to analytically compute expressions for the curvature power spectrum an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…If the dip feature occurs at relatively large scales, say 10 Mpc −1 ≤ k dip ≤ 10 4 Mpc −1 , the properties of the resulting curvature spectrum can be probed through CMB µ−distortions, using well controlled CMB physics in the linear regime [58,59] (see [60,61] for a review). This possibility was suggested in [20], building on the ideas first developed in [21]. In this section we further develop and extend these arguments.…”
Section: Cmb µ-Distortions and Non-gaussianity Around The Dipmentioning
confidence: 75%
See 4 more Smart Citations
“…If the dip feature occurs at relatively large scales, say 10 Mpc −1 ≤ k dip ≤ 10 4 Mpc −1 , the properties of the resulting curvature spectrum can be probed through CMB µ−distortions, using well controlled CMB physics in the linear regime [58,59] (see [60,61] for a review). This possibility was suggested in [20], building on the ideas first developed in [21]. In this section we further develop and extend these arguments.…”
Section: Cmb µ-Distortions and Non-gaussianity Around The Dipmentioning
confidence: 75%
“…First, the spectrum as a function of momentum does not grow faster than k 4 in its way towards the peak [18], see for example Fig 1. Second, the growth of the spectrum is preceded by a pronounced dip, whose position is controlled by the total enhancement of the spectrum [19]. In [20], building on the original idea of [21], we showed that large squeezed non-Gaussianity in proximity of the dip of the spectrum induces sizeable cross-correlations between CMB µ-distortions and temperature fluctuations, which can be used as a test of PBH scenarios based on single-field inflation. Interestingly, this proposal is based only on well understood perturbation theory at large cosmological scales, and does not need to consider complex non-linear phenomena occurring at PBH formation.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations